Between danger and opportunity: Indonesian and forests in an era of economic crisis and political change - Sunderlin, William D. (1999)
Policy aiming to improve the conservation and management of tropical forests are often based on the assumption of political economic stability. Yet some of the most important changes in conditions affecting tropical forests can occur when the political and economic climate changes in abrupt, unpredicted, and largely uncontrolled manner. This fact is illustrated through preliminary, largely media-based documentation of changes underway in Indonesia. It is unclear, as yet, whether the effects of the sudden transformation on the forest sector in this country will be largely positive or negative